Kerukunan Dalam Beragama: Koeksistensi Antar Agama Dalam Upacara Rambu Solo Tana Toraja - Syamsul Alam (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2023)
Harmony between religions is an important foundation in building a harmonious and inclusive society. One concrete example of this harmony can be found in the practice of the Rambu Solo ceremony in Indonesia. The Rambu Solo ceremony is a death ritual performed by the Toraja people in South Sulawesi. Although this ceremony originates from the tradition of the Toraja people who adhere to animism, its practice accommodates the diversity of religions in Indonesia. This paper aims to see how the practice of coexistence between religions is manifested in the Rambu Solo ceremony in Tana Toraja. This research is a qualitative research using primary data. As for the data obtained, namely by directly witnessing the implementation of the Rambu Solo ceremony and conducting interviews, namely a question-and-answer process carried out in a structured manner to obtain data related to what will be studied. The results of the research show that, in the Rambu Solo ceremony, there is a strong coexistence between animism, Protestant Christianity, and Islam. The Toraja family, who follow an animist religion, believe that the spirits of the dead must be guided to a better life after death. They involve traditional leaders in this ceremony. However, with the influence of Protestant Christianity and Islam in the region, elements from these two religions were also incorporated into the Rambu Solo ceremony. Interfaith coexistence in the Rambu Solo ceremony is reflected in the active participation of the local community. Not only are members of the Toraja tribe who are animists involved, but also members of other tribes who follow Christianity or Islam. Local people work together to prepare this ceremony, respecting each other's religious differences. Harmony in religion in the context of the Rambu Solo ceremony has a positive impact on society. This practice strengthens social bonds, strengthens interreligious relations, and creates mutual respect and tolerance. It is also an inspiring example for countries with high religious diversity to promote harmony and coexistence in everyday life.